The Limits of Remaining Market-Neutral: A case study of a hedge fund’s operational strategy - Askmalm,Albert; Lyu,Diwei; Rosenmüller Nordlander,Tove (2025)
The inauguration of President Trump in 2025 led to drastic changes in the U.S. market, notably great political as well as economical risks and uncertainties. The U.S. equity market was struck heavily by the policies, which also heavily affected global equity markets. In this case study, we study a long-short, market-neutral hedge fund situated in London, specifically HAFP (a pseudonym for the interviewed hedge fund to ensure anonymity). Namely, understanding how such a hedge fund understands the current situation, what implications that has on a hedge fund, how they manage the situation and whether they benefitted or lost from the situation. Previous research indicates how some market-neutral hedge funds are exposed to market risks, which should not be viable in theory. To further this observation, we studied and found that when the market was in panic, stock prices dropped dramatically below their fair value, making it difficult to find short ideas. This forces hedge funds to tilt towards the long side and no longer be exactly neutral. We further investigate how hedge funds are affected in the event of high uncertainty caused by political leaders. Our findings show that it has become more difficult for hedge funds to conduct scenario analysis due to unknown/unknown, the influence is also likely to persist as long as the leader responsible is still in charge. We suggest that in response, hedge funds should adopt non-directional strategies, long-term orientation and bottom-up approach, especially as it reduces the noise when seeking stocks and making decisions. The contributions of this paper is showing not only the returns of hedge funds during volatile market conditions, but how they got there. In previous research the concept of strategic flexibility has had a broad definition. In this paper, based on previous research, we use the definition: Strategic flexibility extends beyond being adaptable and agile, rather it is the ability to change direction when needed, whilst having the discipline to stay on track with strategic goals. Strategic flexibility has not been studied on hedge funds before and want to extend the research. We interpret that HAFP possesses traits of strategic flexibility during market fluctuations. We do however observe that strategic flexibility takes a different form in HAFP. As hedge funds would not change their core strategy, in this case market-neutrality, the strategic flexibility therefore lies in the smaller adaptations. In times of market stress or volatility, HAFP’s approach allows them to stay strategically consistent while remaining operationally adaptive, and whilst other firms need to balance flexibility and control, for HAFP this translates into the balance between risk and return. Lastly, risk and opportunity were found to be intertwined, as HAFP views short run volatility as a mediator for long run strategic investments by the bottom-up model. Hedge funds also seem to be able to benefit from the situation by anti-herding, while it is difficult to judge to what extent.
Keywords: political risk; political uncertainty; market-neutral; bottom-up; herding; strategic flexibility